KORELASI ANTARA KADAR LEPTIN DENGAN PROFIL LIPID DAN FREE FATTY ACID PADA SIROSIS HATI - , SITI MARYANI, dr.Neneng Ratnasari, SpPD-KGEH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Malnutrition is a common condition in liver cirrhotic patients. Leptin was regulated physiologically body wieght by suppressing appetite and increasing energy expenditure. Leptin is higher in female than male. Several studies have shown correlation between leptin with metabolic factors like body mass index and lipid profile in cirrhotic patients. In this study, we investigate the correlation between leptin levels with lipid profile and free fatty acid in male liver cirrhotic patients. The hypothesis was there is a correlation between leptin level with lipid profile and free fatty acid in male liver cirrhotic patients. The design is cross sectional study. This study was conducted at Gastroenterohepatology clinic and Interna Ward at Sardjito General Hospital, Yogyakarta. Inclusion criterias were patients with liver cirrhosis â¥ 18 years old , male, Child-Pugh classification B and C, and obtained informed consent. Exclusion criterias were liver cirrhotic patients with comorbidity chronic kidney disease, chronic heart failure, diabetic, cancer, infection/septic, pregnancy, breast feeding, and steroid user. Data collecting was done by anamnesis, physical examination, abdominal ultrasonography examination, and chemical blood test. Statistic methods was used correlation analysis with Pearson test. The result of this study was shown negative correlations that statistically non significant between leptin level and total cholesterol, HDL and triglyseride in male liver cirrhotic patients with correlation coefficient (cholesterol: r= -0,052